2019
DOI: 10.1371/journal.pone.0209588
|View full text |Cite
|
Sign up to set email alerts
|

Cophylogenetic analysis suggests cospeciation between the Scorpion Mycoplasma Clade symbionts and their hosts

Abstract: Scorpions are predator arachnids of ancient origin and worldwide distribution. Two scorpion species, Vaejovis smithi and Centruroides limpidus, were found to harbor two different Mollicutes phylotypes: a Scorpion Mycoplasma Clade (SMC) and Scorpion Group 1 (SG1). Here we investigated, using a targeted gene sequencing strategy, whether these Mollicutes were present in 23 scorpion morphospecies belonging to the Vaejovidae, Carboctonidae, Euscorpiidae, Diplocentridae, and Buthidae families. Our results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 87 publications
2
25
3
Order By: Relevance
“…Based on this phylogenetic information, a discriminant phenotype (spirochete morphology and inhabitant of the spider midgut including the diverticular tissue; Figure 6E), and its high prevalence in all three social Stegodyphus species (Figures 3, 4), we propose ASV_3 to represent a novel species within a novel genus, with the tentative name Candidatus Arachnospira stegodyphi (GenBank accession number for the full length 16S rRNA sequence: MH627299). Finally, ASV_4 groups with ASV_26 and a >99% identical sequence from the African sub-social spider Stegodyphus tentoriicola as a novel, presumably Stegodyphus-specific sister genus to the recently described Scorpion Mycoplasma Clade (Bolaños et al, 2019). These two clusters may delineate arachnid-specific evolutionary lineages of Mycoplasma, a typically host-associated bacterial group without cell wall and often intracellular infections (Brown et al, 2015); in the spider gut, they lined the gut epithelium and could either be located extracellularly or inside the apical border of the epithelium cells ( Figure 6F).…”
Section: Social Spider Microbiomes Resemble Those Of Social Insects Amentioning
confidence: 85%
“…Based on this phylogenetic information, a discriminant phenotype (spirochete morphology and inhabitant of the spider midgut including the diverticular tissue; Figure 6E), and its high prevalence in all three social Stegodyphus species (Figures 3, 4), we propose ASV_3 to represent a novel species within a novel genus, with the tentative name Candidatus Arachnospira stegodyphi (GenBank accession number for the full length 16S rRNA sequence: MH627299). Finally, ASV_4 groups with ASV_26 and a >99% identical sequence from the African sub-social spider Stegodyphus tentoriicola as a novel, presumably Stegodyphus-specific sister genus to the recently described Scorpion Mycoplasma Clade (Bolaños et al, 2019). These two clusters may delineate arachnid-specific evolutionary lineages of Mycoplasma, a typically host-associated bacterial group without cell wall and often intracellular infections (Brown et al, 2015); in the spider gut, they lined the gut epithelium and could either be located extracellularly or inside the apical border of the epithelium cells ( Figure 6F).…”
Section: Social Spider Microbiomes Resemble Those Of Social Insects Amentioning
confidence: 85%
“…Although strict cospeciation seems rather rare (de Vienne et al, 2013), in mutualisms it was described repeatedly, for example, between arthropods and their endosymbionts (Bolaños et al, 2019;Degnan, Lazarus, Brock, & Wernegreen, 2004;Hosokawa, Kikuchi, Nikoh, Shimada, & Fukatsu, 2006), in specialized ant-plant mutualisms (Chomicki, Ward, & Renner, 2015), and fig-pollinating wasps and figs (Cruaud et al, 2012;Jousselin et al, 2008). Alternatively, species diversification in mutualisms can also be facilitated by partner switches like in pollination mutualisms (Janz, Nyblom, & Nylin, 2001;Kawakita, Takimura, Terachi, Sota, & Kato, 2004) or ant-plant associations (Quek, Davies, Itino, & Pierce, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A metagenome-assembled genome study of gut microbial Mycoplasma in salmonoids revealed that the intestinal commensal Mycoplasma actively metabolizes using ammonia [ 38 ]. However, little is known about their role in invertebrate microbiomes, other than a study reporting a potential symbiotic relationship in scorpions [ 43 ]. We suspect that cephalopods may also have symbiotic relationships with gut Mycoplasma through ammonia metabolism, as in the case of salmonoids, because cephalopods are both carnivorous and ammonotelic.…”
Section: Discussionmentioning
confidence: 99%